Perfil epidemiológico e complicações pós-cirúrgicas do transplante renal no estado do Pará - período de 1999 a 2004 - MIYAHARA, Gilberto Akira (2022)
Nowadays, the renal transplant is the best treatment option for end-stage disease patients. In comparison with other therapeutic forms, as the dialysis peritoneal and the hemodialyse, the renal transplant offers to the patient a better quality, rehabilitation and life expectative. The objective of this study is to verify the profile epidemic and some mainly post-transplantation surgical complications in kidney transplant. The methodology was a descriptive epidemic study of the traverse type with the statistical analysis of picked data of the patients' handbooks transplanted renal of the Ofir Loyola Hospital, in Pará, from August 1999 to December 2004. Accord to the method studied, the number of renal transplants surgeried was 150, wich 49% was made with graft from of live donor (n=74) and 51% from donor cadaveric (n=76). The masculine sex and the age group between 35 and 49 years represents the largest number of patients, with 60,6% and 34%, respectively. The immunosuppressive outline more used by the service is the association among cyclosporin A + prednisona + azatioprina (58%). The predominant disease of the end-stage renal failure was the chronic glomerulonefrite, with 34%. It is important to emphasize the straight control of hypertensive pathologies, diabetes and the dislipydemia, due the high occurrence (25%) as etiology of IRCT. The total incidence of renal post-transplant surgical complications was of 34%, wich the collections perirrenais was 15,3%, the urologic complications 9,3%, the vascular complications 0,6% and the other complications 8,6%. The agute rejection occurred in 31% (n=47) of the patients. In conclusion, all the observed data were compatible with the results of most of the consulted literature, being very interesting for the service of renal transplant from the Ofir Loyola Hospital keep on working and developing this kind of program.